Prevention of autoimmune demyelination in non-human primates by a cAMP-specific phosphodiesterase inhibitor. - Genain, C P (1995)
Experimental allergic encephalomyelitis (EAE) is an autoimmune disease of the central nervous system that serves as a model for the human disease multiple sclerosis. We evaluated rolipram, a type IV phosphodiesterase inhibitor, for its efficacy in preventing EAE in the common marmoset Callithrix jacchus. In a blinded experimental design, clinical signs of EAE developed within 17 days of immunization with human white matter in two placebo-treated animals but in none of three monkeys that received rolipram (10 mg/kg s.c. every other day) beginning 1 week after immunization. In controls, signs of EAE were associated with development of cerebrospinal fluid pleocytosis and cerebral MRI abnormalities. In the treatment group, there was sustained protection from clinical EAE, transient cerebrospinal fluid pleocytosis in only one of three animals, no MRI abnormality, and marked reduction in histopathologic findings. Rolipram-treated and control animals equally developed circulating antibodies to myelin basic protein. Thus, inhibition of type IV phosphodiesterase, initiated after sensitization to central nervous system antigens, protected against autoimmune demyelinating disease.